Advances in Multiple Stimuli-Responsive Drug-Delivery Systems for Cancer Therapy - Jia R (Dove Medical Press, 2021)
Ruixin Jia,1,* Lesheng Teng,2,* Lingyu Gao,1 Ting Su,1 Lu Fu,3 Zhidong Qiu,1 Ye Bi1,4 1College of Pharmacy, Changchun University of Chinese Medicine, Changchun, Jilin, People’s Republic of China; 2School of Life Science, Jilin University, Changchun, Jilin, People’s Republic of China; 3College of Life Science, Jilin Agricultural University, Changchun, Jilin, People’s Republic of China; 4Practice Training Center, Changchun University of Chinese Medicine, Changchun, Jilin, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ye BiPractice Training Center, Changchun University of Chinese Medicine, 1035 Boshuo Road, Changchun, Jilin, People’s Republic of ChinaTel/Fax +86-431-86763979Email biye88@outlook.comZhidong QiuCollege of Pharmacy, Changchun University of Chinese Medicine, 1035 Boshuo Road, Changchun, Jilin, People’s Republic of ChinaTel/Fax +86-431-86763979Email qzdcczy@163.comAbstract: Nanomedicines afford unique advantages in therapeutic intervention against tumors. However, conventional nanomedicines have failed to achieve the desired effect against cancers because of the presence of complicated physiological fluids and the tumor microenvironment. Stimuli-responsive drug-delivery systems have emerged as potential tools for advanced treatment of cancers. Versatile nano-carriers co-triggered by multiple stimuli in different levels of organisms (eg, extracorporeal, tumor tissue, cell, subcellular organelles) have aroused widespread interest because they can overcome sequential physiological and pathological barriers to deliver diverse therapeutic “payloads” to the desired targets. Furthermore, multiple stimuli-responsive drug-delivery systems (MSR-DDSs) offer a good platform for co-delivery of agents and reversing multidrug resistance. This review affords a comprehensive overview on the “landscape” of MSR-DDSs against tumors, highlights the design strategies of MSR-DDSs in recent years, discusses the putative advantage of oncotherapy or the obstacles that so far have hindered the clinical translation of MSR-DDSs.Keywords: multi-stimuli responsive nanoparticles, drug delivery, tumor microenvironment, oncotherapy